Determination of the impact of the load on buildings for the subsequent optimal choice of the organizational and technological solution of the construction project - Тугай, О.А.; Samaha, Toni (Ways to Improve Construction Efficiency, 2022)
The present document helps to determine the impact of loads on buildings for the subsequent optimal choice of the organizational and technological solution of the construction project. In further studies it is shown that the effect of loads has a major influence on the process of construction and the optimization of the time cost efficiency. The known literatures describe the loads as a statistical variable which is related to the local, environmental and useable conditions of the project. All types of loads, static and dynamic, directly reduce or increase the cost of the project, it depends of the consideration taken during the design. For example, the main variable that will be considered in this document is the soil effect on the cost of the structure under static and dynamic loads, if it is taken or not into account during the design of the superstructure, and how it changes the whole behavior of any structure making it more rigid or more flexible. A particular study is done here down in this document showing the effects of soil on two different buildings during a dynamic impact (seismic event in our case). Moreover, this document provides with the needed formulas and tools to describe the soil material in 3D design softwares. The use of these tools will let the structural designer to change the response spectra curve and reduce the influence of the dynamic impact on the building. Thus, a comparative table will show the difference between the use of rigid base models and flexible ones to spotlight the effects of the soil. Furthermore, a sensitivity study is done showing the contribution part of some formulas in the soil consideration. The reduction in the base shear will allow the client and contract to reduce the budget of the project and by this an optimization of the constructional time can be done.